Density of low-barrier opioid agonist clinics and risk of non-fatal overdose during a community-wide overdose crisis: A spatial analysis. (August 2019) - Amram, Ofer; Socías, Eugenia; Nosova, Ekaterina; Kerr, Thomas; Wood, Evan; DeBeck, Kora; Hayashi, Kanna; Fairbairn, Nadia; Montaner, Julio; Milloy, M.J.
Abstract: Objectives: In recent years, North America has witnessed a spike in the number of overdoses (OD) and OD-related deaths. The aim of this study was to assess spatial correlates of OD risk in Vancouver, Canada. Methods: Data utilized for this study was from three open and ongoing prospective cohorts of people who use drugs (PWUDs) in Vancouver, Canada. Logistic regression analyses with generalized linear mixed-effects models (GLMM) was used to examine correlates of residing in areas characterized by high OD rates. Mapping was used to examine areas showing OD clusters. Results: We included 1336 PWUDs who resided in the downtown area. In multivariable analysis, higher availability of methadone clinics within walking distance, daily cocaine injectors and daily crack users had independent decreased odds of living within an OD cluster. Conclusion: This study found that higher availability of methadone clinics was associated with decreased odds of living within OD clusters.